Analisa Tebal Perkerasan dengan Menggunakan Material Kinang Jingkion - Idie, Johanis Hs Ervans (Syntax Literate, 2023)
The purpose of this study is 1) Analyzing the Pavement Layer Thickness using Kinang Jingkion material. 2) Calculating the Compaction Layer for CBR by pressing the Kinang Jingkion material. The local Kinang Jingkion material used in this study as a surface layer was taken from a location in the Yalimo Regency of Papua Province. As for Kinang Jingkion material, it is located in Habie River, Yahukimo Regency with a geographical point of 03o45'56.63" South Latitude and 139o23'26.19'' North Latitude. Perimer data is data taken directly by researchers by digging the original source of the object under study. In analyzing the thickness of the pavement with the Component Analysis method, the surface layer can be combined with the Class A Foundation Layer is 9 cm and the Class B Foundation Layer is 6 cm. The Compaction Layer for CBR which is used as a covering layer is In calculating the CBR Compaction Layer divided into 2 stages, namely: a) Field CBR is taken data on 2 km of road sections taken as many as 20 test points with an average CBR value of 80.04%. b) Laboratory CBR in laboratory CBR testing of 3 compaction tests in CBR with an average of 18%.